Analisa Persespsi Masyarakat Pendatang Terhadap Kearifan Lokal Metode Fuzzy Inference System (FIS) Mamdani - Silky Safira; Wifra Safitri (Jurnal KomtekInfo, 2019)
Fuzzy logic is considered capable of mapping input into output without ignoring existing factors. Fuzzy logic is very flexible and tolerant of existing data. By using fuzzy logic, a model will be produced from a system that is able to estimate the perceptions of immigrants to local wisdom. The factors that influence the determination of immigrants' perceptions of local wisdom with fuzzy logic are the attitude of immigrant communities. Society's socio-cultural life is shown by the many links to other social life, such as ideology, lifestyle, and economy. This means that changes in one socio-cultural life will affect other social and cultural lives. Therefore this system is made so that the public can know, study and examine the variety of local wisdom, examine the role of indigenous and immigrant people in preserving local wisdom and study the strategies of indigenous and immigrant populations in limiting conflict and so on by applying fuzzy mamdani methods that are expected to provide decisions good in responding to the perceptions of immigrants towards local wisdom in West Kinali Pasaman.